2007
DOI: 10.1007/s10648-007-9059-y
|View full text |Cite
|
Sign up to set email alerts
|

Attributions of Productive Authors in Educational Psychology Journals

Abstract: Are there similarities in the writing approaches and practices among the topproducing authors in our field? If so, perhaps knowing this information may benefit graduate students or recent graduates. In this paper, I asked 13 authors to explain why they were so productive in terms of publishing in educational psychology journals. Four categories of authors' attributions for productivity were identified: collaboration, passion/ curiosity, research skills, and time management. All categories were consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 7 publications
(7 reference statements)
5
34
0
3
Order By: Relevance
“…However, this diversity makes it an extremely challenging, stimulating and rewarding job where you have options available to you and have some choice in your main 4 focus and direction of your career. Consistent with previous research, I found the task of balancing the time demands of these various roles can be difficult and has lead to the availability of time being seem as a major obstacle for academic career progression (Halpern, 2008;Mayrath, 2008) that highlights the need for effective time management. Some methods proposed to help create time and maximise efficiency include limiting classroom preparation time, setting meeting boundaries, conducting group advising sessions, trying to integrate teaching and research, removing any distractions, planning daily writing time and creating deadlines for yourself (Mayrath, 2008;McCormack & Barnes, 2008).…”
Section: Initial Considerationssupporting
confidence: 79%
See 2 more Smart Citations
“…However, this diversity makes it an extremely challenging, stimulating and rewarding job where you have options available to you and have some choice in your main 4 focus and direction of your career. Consistent with previous research, I found the task of balancing the time demands of these various roles can be difficult and has lead to the availability of time being seem as a major obstacle for academic career progression (Halpern, 2008;Mayrath, 2008) that highlights the need for effective time management. Some methods proposed to help create time and maximise efficiency include limiting classroom preparation time, setting meeting boundaries, conducting group advising sessions, trying to integrate teaching and research, removing any distractions, planning daily writing time and creating deadlines for yourself (Mayrath, 2008;McCormack & Barnes, 2008).…”
Section: Initial Considerationssupporting
confidence: 79%
“…Consistent with previous research, I found the task of balancing the time demands of these various roles can be difficult and has lead to the availability of time being seem as a major obstacle for academic career progression (Halpern, 2008;Mayrath, 2008) that highlights the need for effective time management. Some methods proposed to help create time and maximise efficiency include limiting classroom preparation time, setting meeting boundaries, conducting group advising sessions, trying to integrate teaching and research, removing any distractions, planning daily writing time and creating deadlines for yourself (Mayrath, 2008;McCormack & Barnes, 2008). It is also necessary to say "no" at times (Kiewra, 2008) since you can be asked to fulfil many commitments but have limited time to complete them all in and your attention can become diluted to the point where you have many goals but don"t get round to achieving them.…”
Section: Initial Considerationssupporting
confidence: 79%
See 1 more Smart Citation
“…Murray (2013) suggests that scholars move between series of engagements and disengagements. Disengagement from other activities (MAYRATH, 2008) is necessary to success in publishing, and competing demands from the academic work can represent an impediment to writing (MACLEOD; STECKLEY; MURRAY, 2012). Murray's Model of Disengagement (2013) suggests considering that engagement involves:…”
Section: Writing For Publication; Literaturementioning
confidence: 99%
“…Podejście jakościowe preferowane jest najczęściej w takich miękkich dyscyplinach jak na przykład psychologia nauczania (Mayrath 2008, Kiewra i Creswell 2000, Patterson i Kiewra 2013, Martinez i in. 2011.…”
Section: Wysoce Produktywni Naukowcy: Przegląd Literaturyunclassified